High-resolution stable isotope profiles from shells of the land snail Placostylus reveal contrasting patterns between snails originating from New Zealand and New Caledonia - Quenu M; Judd EJ; Morgan-Richards M; Trewick SA; Holt K; Tyler J; Lorrey AM (John Wiley and Sons Ltd, 2023)
The stable oxygen (δ18Oshell) and carbon (δ13Cshell) isotope ratios retrieved from the carbonate shell of terrestrial gastropods can be used as an environmental proxy and are thought to reflect dietary composition and ambient climatic conditions (e.g. precipitation amount, humidity, temperature). Here, we generate high-resolution isotopic profiles of nine modern land snails of the genus Placostylus, collected from two locations in New Caledonia and one location in New Zealand. We found that snails from New Zealand had, on average, higher δ18Oshell values than their counterparts in New Caledonia, which surprisingly runs counter to the expected relationship based on the isotopic composition of rainwater between these two regions. Specimens from New Caledonia exhibit ephemeral decreases in their δ18Oshell values, which could be linked to extreme precipitation events in this region, while snails from New Zealand have less variation in their δ18Oshell values. Snails from New Zealand had, on average, slightly higher δ13Cshell than their counterparts in New Caledonia, but a large difference in carbon isotopes was sometimes observed between snails collected at the same location. Most snails exhibit a temporal trend in their δ13Cshell values, indicating potential shifts in diet through to maturity.
Keywords: Carbonate shell; Placostylus; southwest Pacific; stable isotopes; terrestrial gastropods